The Role of Customer Experience, Service Quality, and Customer Satisfaction on Consumer Loyalty - Arie Wahyu Prananta; I Wayan Suyadnya; Indra Jaya Kusumawardana; Zainal Abidin (Malaqbi Publisher, 2026)
Customer loyalty has become a crucial determinant of organizational sustainability in today's highly competitive business environment. This study aims to examine the role of customer experience, service quality, and customer satisfaction in influencing consumer loyalty. A quantitative research approach was employed using a cross-sectional survey design. Data were collected from 200 consumers through a structured questionnaire using a purposive sampling technique. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that customer experience and service quality have significant positive effects on customer satisfaction. Furthermore, customer experience, service quality, and customer satisfaction each have significant positive effects on consumer loyalty. Among these variables, customer satisfaction was identified as the strongest predictor of consumer loyalty. The mediation analysis further reveals that customer satisfaction partially mediates the relationships between customer experience and consumer loyalty as well as between service quality and consumer loyalty. These findings suggest that organizations seeking to enhance customer loyalty should focus on creating positive customer experiences, delivering high-quality services, and consistently improving customer satisfaction. The study contributes to the customer relationship management literature by providing empirical evidence of the interrelationships among customer experience, service quality, customer satisfaction, and consumer loyalty within a comprehensive research framework. The findings also offer practical implications for managers in developing customer-centered strategies that strengthen long-term customer relationships and improve organizational competitiveness.